Distress, depression, anxiety, and somatization scores in veterans with PTSD and mild traumatic brain injury after an 8-week comprehensive intervention - Smashna, Олена (Psychosomatic Medicine and General Practice, 2021)
Background. Understanding the complex relationships between combat injuries, physical health, and mental health symptoms is critical to meeting the healthcare needs of veterans. The relationship between head injuries, posttraumatic stress disorder (PTSD), and depression among combat-injured service members is unique to modern conflicts but understudied. Research suggests a relationship between PTSD and somatic complaints in veterans, suggesting that PTSD influences somatic complaints through underlying symptoms of depression and anxiety sensitivity. Aims. To investigate the dynamics of distress, depression, anxiety, and somatization in veterans with PTSD and mTBI after an 8-week comprehensive intervention (combining a psychotherapy program with transcranial direct current electrical stimulation (tDCS)). Methods. The data of the initial and repeated examination of 329 veterans from three clinical groups were analyzed: individuals with PTSD (n=109), with mild TBI (n = 112), and with PTSD+TBI comorbid condition (n=108). All patients received standard therapy as well as psychotherapeutic intervention and transcranial direct current electrical stimulation (tDCS). The Four-Dimensional Symptom Questionnaire (4DSQ) was used to assess distress, depression, anxiety, and somatization. The rank correlation between the primary and repeated examination data for each clinical group was also determined. Results. Patients suffering from PTSD or PTSD with mTBI had significantly more symptoms of depression, anxiety, and somatization than patients with mTBI without PTSD. After the therapy, patients from the PTSD and PTSD+mTBI groups experienced a subjective increase in the feeling of distress, which was associated with a reduction of mainly depressive and somatoform symptoms in the respondents of the PTSD+mTBI group, and in patients with PTSD with a decrease of mainly depressive and anxiety symptoms. In contrast, in the patients with TBI, there was no increase in the subjective feeling of distress, and the improvement of the mental state was accompanied by a decrease in the entire investigated spectrum of symptoms - depressive, somatoform, and anxiety. In patients with TBI, a higher level of distress at the primary examination led to a lower level of depression and distress at the repeated examination, and a high somatization score was correlated with its significant reduction under the influence of therapy. In the patients of the PTSD+mTBI group, a high index of somatization at the primary examination was correlated with a subjective increase in distress, but a decrease in somatization itself at the end of therapy. Conclusions. The presence and level of expressiveness of symptoms of distress, depression, anxiety, and somatization in persons with PTSD, TBI, and a combination of these painful conditions are closely related to the effectiveness of the complex intervention, which provides the possibility of differentiated targeted therapy of individual clinical groups of patients.